Randomized clinical trial comparing 10‐ or 14‐day sequential therapy and 10‐ or 14‐day concomitant therapy for the first line empirical treatment of Helicobacter pylori infection. Issue 3 (March 2017) - Park, Sung Min; Kim, Joon Sung; Kim, Byung‐Wook; Ji, Jeong‐Seon; Choi, Hwang
Abstract: Background and Aim: Whether concomitant therapy is superior to sequential therapy (ST) as first‐line therapy of Helicobacter pylori in areas with high clarithromycin resistance remains controversial. The aim of this study was to compare the efficacy and tolerability of 10‐ or 14‐day ST with 10‐ or 14‐day concomitant therapy (CT). Methods: This was a prospective randomized study comparing 10‐ or 14‐day ST with 10‐ or 14‐day CT. The ST‐10 and ST‐14 groups received pantoprazole 40 mg and amoxicillin 1 g twice a day for the first 5 and 7 days followed by pantoprazole 40 mg, clarithromycin 500 mg, and metronidazole 500 mg twice a day for the remaining 5 and 7 days, respectively. The CT‐10 and CT‐14 groups received pantoprazole 40 mg, amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg twice daily for 10 and 14 days, respectively. Results: Three hundred forty‐one patients were randomly allocated to the four groups. The modified intention‐to‐treat eradication rates of ST‐10, ST‐14, CT‐10, and CT‐14 were 91.7%, 91.2%, 94.2%, and 98.5%, respectively. The corresponding per protocol eradication rates were 91.4%, 91.0%, 95.6%, and 98.5%. There was no difference in compliance and adverse events in the four groups. Eradication rates increased sequentially with statistical significance in the following order: ST‐10, ST‐14, CT‐10, and CT‐14 ( P  = 0.044). Conclusions: All four regimens achieved eradication rates >90% in per protocol analyses in a country with high clarithromycin resistance. There was no difference in tolerability among the four regimens.